Investigation on Dynamics Characteristic of Multilayer Steel Plate Impacted by Projectile - Ibrahim, Mohd Norihan; Samian, Uma Isma; Kamarudin, Kamarul-Azhar; Ismail, Al Emran; Jamian, Saifulnizan; Mohd Nor, Mohd Khir; Awang, Muhamad Khairudin; Adi Siswanto, Waluyo (International Journal of Integrated Engineering, 2019)
The paper describes a work focused on the process of perforation of multilayer advanced high strength steel (AHSS). A numerical investigation has been carried out to analyze in details the perforation process subjected to normal impact by different nose shapes of projectiles. The perforation process has been simulated by the application of 3D analysis using IMPACT dynamic FE program suite. The comparison on failure modes depending on the projectile nose shape have been studied and evaluated. An appropriate constitutive relation was applied to describe the material behaviour of the multilayer target plate. The study covered different failure modes of perforated advanced high strength steel (AHSS) sheet according to different level of impact velocity ranging from 22 m/s to 78 m/s. The blunt projectile impact towards multilayer target plate leads to generation of plug formation and fragmentation while hemispherical projectile impact shows almost similar petals formation between first, second and third layer.